(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
PROLOGUE "The man who farms as his forefathers did cannot produce much food no matter how rich the land or how hard he works. The farmer who has access to and knows how to use what science knows about soils, plants, animals, and machines can produce abundance of food though the land be poor. Nor need he work nearly so hard and long. He can produce so much that his brothers and some of his neighbours will move to town to earn their living." ––T W Schultz (1964) (Noble Prize winner for Economics, 1979) Dear friends and colleagues, at some point, I will come back to this statement by Prof. Theodore Schultz. That is all I say about that for now.